How attention factors into executive function in preschool children - Deodhar, Aditi V.; Bertenthal, Bennett I. (Frontiers in Psychology, 2023)
Executive Function consists of self-regulation processes which underlie our ability to plan, coordinate, and complete goal-directed actions in our daily lives. While attention is widely considered to be central to the emergence and development of executive function during early childhood, it is not clear if it is integral or separable from other executive function processes. Previous studies have not addressed this question satisfactorily because executive function and attention are multidimensional constructs, but they are often studied without differentiating the specific processes that are tested. Moreover, some studies consist of only one task per process, making it difficult to ascertain if the pattern of results is attributable to different processes or more simply to task variance. The main aim of this study was to more fully investigate how attention factored into the underlying structure of executive function in preschool children. Preschool children (n=137) completed a battery of tasks which included executive function (i.e., response inhibition, working memory) and attentional control (i.e., sustained attention, selective attention) processes; there were two tasks per process. Confirmatory factor analyses (CFA) were conducted to test which of three models fit the data best: (1) a unitary one-factor model with attention loading onto the same factor as other executive function processes, (2) a two-factor model with attention loading onto a separate factor than other executive function processes, or (3) a three-factor model with attention, response inhibition, and working memory as separate factors. Fit indices and model comparisons indicated that the two-factor model fit the data best, suggesting that attentional control and executive function were related, but separable. Although this study is not the first to advocate for a two-factor model during the preschool years, it is the first to suggest that the two factors are attentional control and executive function, not working memory and response inhibition. One important implication of these findings is that a complete assessment of executive function during the preschool years necessitates measuring not only response inhibition and working memory, but attentional control as well.